in Set Theory & Algebra recategorized
346 views
0 votes
0 votes

The functions mapping $R$ into $R$ are defined as :

$f\left(x \right)=x^{3} - 4x, g\left(x \right)=\frac{1}{x^{2}+1}$ and $h\left(x \right)=x^{4}.$

Then find the value of the following composite functions :

$h_{o}g\left(x \right)$ and $h_{o}g_{o}f\left(x \right)$

  1. $\left ( x^{2}+1 \right )^{4}$ and $\left [ \left ( x^{3}-4x \right )^{2}+1 \right ]^{4}$
  2. $\left ( x^{2}+1 \right )^{4}$ and $\left [ \left ( x^{3}-4x \right )^{2}+1 \right ]^{-4}$
  3. $\left ( x^{2}+1 \right )^{-4}$ and $\left [ \left ( x^{2}-4x \right )^{2}+1 \right ]^{4}$
  4. $\left ( x^{2}+1 \right )^{-4}$ and $\left [ \left ( x^{3}-4x \right )^{2}+1 \right ]^{-4}$
in Set Theory & Algebra recategorized
346 views

3 Answers

1 vote
1 vote
option 4

 

h(g(x))=h(1/(x^2 +1)) = (x^2 +1)^ -4

h(g(f(x)))= h(g(x^3 -4x)) = [(x^3-4x)^2+1]^ – 4

1 comment

$f \circ g (x)$  is defined as $f (g (x))$

your answer is correct , please use equation editor to type set equations properly
0
0
1 vote
1 vote

Option D is right

h o g(x) = h(g(x)) = h(1/x2 +1) = (x2+1)-4

h o g o f(x) = h(g(f(x))) = h(g(x3 - 4x)) = h(1/[(x3 - 4x)2 +1]) = [(x3 - 4x)2 +1]-4

1 vote
1 vote

Ans is D

Answer:

Related questions